Pemikiran Teologi Pendidikan Kristian Ignatius Loyola - Natalia Natalia; Aren Kristin; Reonald Mikhel Nicolaus; Sarmauli Sarmauli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Christian education has played a significant role in shaping individual character, thought, and morality across the globe. One of the most influential figures in this field is Ignatius Loyola (1491-1556), founder of the Society of Jesus (Jesuits). Loyola’s educational philosophy, rooted in Catholic spirituality, emphasizes discipline, character formation, and the integration of faith and intellect. The purpose of this study is to explore the theological foundations of Christian education according to Ignatius Loyola, outline the core principles of his educational thought, and examine its relevance to contemporary Christian education. Data were collected through a literature review of books and scholarly articles. Loyola’s approach, known as Ignatian education, focuses on holistic development-spiritual, intellectual, and social-embodied in the principle of